2008
DOI: 10.5330/psc.n.2010-11.335
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Confidentiality with Minors: Dilemmas of School Counselors

Abstract: This article examined the attitudes of 195 school counselors in Israel regarding (a) the decision to maintain or breach confidentiality in a variety of ethical dilemmas, and (b) the reasons given for justifying their decisions. Eighteen ethical dilemmas in three domains were presented to respondents in a questionnaire. School counselors were most willing to breach confidentiality regarding dilemmas in the domain of dangerous behaviors or situations, less willing in the domain of unlawful behaviors, and least w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 14 publications
1
15
0
3
Order By: Relevance
“…Similar to results from the Gibson and Pope and the Tarvydas et al studies, items regarding breach of confidentiality, sexual dual relationships, and violations of boundaries and informed consent were predominantly judged as unethical in this study. Results are also in line with several other studies (Lazovsky, 2008;Moyer & Sullivan, 2008;Neukrug & Milliken, 2011) that find counselors' perceived breach of confidentiality in cases of risky client behavior, such as suicide and violence victimization, as ethical.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to results from the Gibson and Pope and the Tarvydas et al studies, items regarding breach of confidentiality, sexual dual relationships, and violations of boundaries and informed consent were predominantly judged as unethical in this study. Results are also in line with several other studies (Lazovsky, 2008;Moyer & Sullivan, 2008;Neukrug & Milliken, 2011) that find counselors' perceived breach of confidentiality in cases of risky client behavior, such as suicide and violence victimization, as ethical.…”
Section: Discussionsupporting
confidence: 91%
“…Evidently, research (Lazovsky, 2008;Moyer & Sullivan, 2008;Moyer, Sullivan, & Growcock, 2012) suggests that school counselors are more likely to breach confidentiality in cases of risky student behavior. Isaacs and Stone's (1999) study revealed that counselors would breach confidentiality in cases of suicide ideation, violence victimization, substance abuse, theft, depression, and abortion.…”
mentioning
confidence: 95%
“…The comments made by some of the respondents illuminate this reality. While counselors are taught to protect student confidentiality as a principle underlying one of the fundamental roles of the counseling profession (Mitchell et al, 2002), school administrators may expect information regarding an individual student or group of students if the information contains evidence of infractions against school policy (Lazovsky, 2008). While principals in this study supported the practice of personal and social counseling and many suggested a discussion had occurred regarding expectations for disclosure when imminent harms exists, the fact remains that some respondents wanted to know about student issues unrelated to threats of harm or safety.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are few examples of case law that provide clear direction to both school administration and school counselors regarding the practice of confidential communications. School administrators rely on school board policy, legal counsel, or personal decision making (Bradley, 2005), while school counselors rely on accurate interpretation of their professional ethical codes (Lazovsky, 2008).…”
Section: Privileged Communication Lawsmentioning
confidence: 99%
See 1 more Smart Citation